Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Produktivitas Kerja (Survei Pada Karyawan Bagian Produksi Pada CV. Wijaya Family Tasikmalaya) - Endah Julia Indrika; Barin Barlian; Ai Kusmiati Asyiah (GLOBAL SCIENTS PUBLISHER, 2025)
This purposse study to determine and analyze the influence of work discipline and work environment both simultaneously and partially on the work productivity of production employees at CV. Wijaya Family Tasikmalaya. The method used in this study is a survei. With a research sample of 100 production employees as respondents. The data used is primary and secondary data. The analysis tool used in this study is multiple linear regression using the SPSS version.25 support application. The test results show that simultaneously showing the variables used in the study, namely work discipline and work environment, have a significant effect on the work productivity of production employees at CV. Wijaya Family Tasikmalaya. Likewise, partially there is a significant effect of discipline on the work productivity of production employees, and there is a significant effect between the work environment on the work productivity of employees at CV. Wijaya Family Tasikmalaya.